Surface plasmon resonance biosensors for SARS-CoV-2 sensing: The role of silicon nitride and graphene - Talia Tene; Diana Coello-Fiallos; Myrian Borja; Narcisa Sánchez; Fabián Londo; Cristian Vacacela Gomez; Stefano Bellucci (Biosensors and Bioelectronics: X)
We present a systematic optimization and analysis of SPR biosensors, focusing on the influence of design parameters such as silver (Ag), silicon nitride (Si₃N₄), graphene, and ssDNA layer thicknesses. Two configurations, Sys₃ and Sys₅, were developed and numerically evaluated under varying SARS-CoV-2 concentrations in PBS solution, ranging from 0.01 nM to 100 nM. Sys₃, optimized with Ag at 55 nm, Si₃N₄ at 13 nm, and ssDNA at 10 nm, demonstrated exceptional sensitivity (371.7°/RIU), low limit of detection, and high detection accuracy, making it suitable for precision applications. In contrast, Sys₅, incorporating a graphene layer (0.34 nm) alongside Ag at 50 nm, Si₃N₄ at 10 nm, and ssDNA at 10 nm, exhibited superior robustness and a higher figure of merit (2287.2 RIU⁻1), offering consistent performance across a broader dynamic range. These results highlight the versatility of SPR biosensors in adapting to diverse diagnostic needs.